Participation of community in mangrove conservation in coastal area of the Valentine Strait, West Seram, Maluku, Indonesia - MARLON I. AIPASSA; MARTHA E. SIAHAYA; HENDRIK S.E.S. APONNO; YOSEP RUSLIM; ROCHADI KRISTININGRUM (Society for Indonesian Biodiversity, 2023)
Abstract. Aipassa MI, Siahaya ME, Aponno HSES, Ruslim Y, Kristiningrum R. 2023. Participation of community in mangrove conservation in coastal area of the Valentine Strait, West Seram, Maluku, Indonesia. Biodiversitas 24: 2467-2474. A mangrove forest is composed of mangrove plants and constitutes a crucial ecosystem in coastal areas. It is a vital source for maintaining aquatic ecosystems between the sea, coast, and land. Additionally, it provides benefits to humans, such as contributing to a more comfortable climate and weather conditions that can prevent natural disasters. However, the mangrove in the Valentine Strait area (West Seram, Maluku, Indonesia) is threatened by land conversion, leading to damage and loss. Some people are trying to preserve and maintain mangrove in their area. Therefore, the aim of this research was to describe the actions of the local community in the area, using the concept of cultural capital. A combination of qualitative and quantitative methods was used, and both primary and secondary data were collected. Primary data were gathered directly from the research location, while secondary data were obtained through local community information, various websites, and documents related to the management of natural resources. Additionally, key informants, including local community leaders, Kewang, and LPPM Maluku (NGO), were interviewed to collect relevant data on the cultural capital possessed by the community. The data for identifying mangrove species were calculated and tabulated to determine the species density in the Valentine Strait area. Furthermore, the collected community data were analyzed using cultural capital theory. The results indicate that community has started to reapply the concept of cultural capital of the Sasi tradition as ecological knowledge to maintain and preserve mangrove; hence, ensuring conservation in the Valentine Strait area. Mangrove forests have become home to fish, shrimp, and crabs and are also important for birds, primates, and reptiles.